ETUDE DE L’EFFET LARVICIDE DES HUILES ESSENTIELLES DES PLANTES A L’EGARD DE Culex pipiens - GHARBI Marwa; ROUABHIA Amani (My University, 2024)
The aim of this study was to estimate the rates of toxicity following treatment of newly emerged L3Culex pipiens larvae with different concentrations of Allium cepa oil, Aloe vera oil and a mixture (Allium cepa + Aloe vera) under laboratory conditions and in accordance with World Health Organisation (WHO) recommendations. The results showed a significant sensitivity of the treated larvae with increasing concentration of these oils, as well as a toxicity that increased with the duration of treatment. In addition, a comparison was made between: 1. Allium cepa oil and Aloe vera showed that Allium cepa oil was the most effective. 2. Allium cepa oil and the mixture (Allium cepa + Aloe vera) showed that Allium cepa oil was the most effective. 3. Aloe vera oil and the mixture (Allium cepa + Aloe vera) showed that the mixture (of Allium cepa + Aloe vera) was effective. 4. Allium cepa oil, Aloe vera and the mixture (Allium cepa + Aloe vera) showed that Allium cepa oil was the most effective. Toxicity tests conducted showed that these oils have insecticidal properties and Allium cepa oil is the most effective compared to Aloe vera oil and the mixture consisting of (Aloe vera + Allium cepa). ------------------------------------------------------------------------------------------------------------------------------------- يهـدف هذا العمل إلى تقديــر نسب التأثير السمي بعد المعاملة ليــرقات الطور الثالث لبعوض Culex pipiens بتـراكيزمختلفــة من زيتالبصل، زيت الصبار ومزيج (البصل +الصبار)وهذا تحت الظروف المخبرية وتوصيات المنظمة العالمية للصحة (OMS) النتائج بينت وجود حساسية كبيرة لليرقات المعاملة مع زيادة التركيز لهذه الزيوت، كذلك السمية تزداد كلما كانت مدة المعاملة أطـــول كذلك المقارنة بين: 1. زيت البصل والصبار بينت أن زيت البصل هو الفعال. 2. زيت البصل ومزيج (البصل +الصبار (بينت أن زيت البصل هو الفعال. 3. زيت الصبار ومزيج (البصل + الصبار (بينت أن المزيج هو الفعال. 4. زيت البصل، الصبار ومزيج (البصل +الصبار (بينت أن زيت البصل هو الفعال. اختبارات السمية التي أجريت بينت أن هذه الزيوت تملك خصائص مبيد حشري، وأن زيت البصل هو الفعال مقارنة ببقية الزيوت -------------------------------------------------------------------------------------------------------------------------------------- Cette étude vise à estimer les proportions de l’effet toxique après traitement des larves L3 nouvellement exuvies de Culex pipiens à différentes concentrations d'huile d’Allium cepa, d'huile d'Aloe vera et d'un mélange (Allium cepa+ Aloe vera) dans des conditions de laboratoire et selon les recommandations de l'Organisation Mondiale de la Santé (OMS). Les résultats ont montré une sensibilité significative des larves traitées avec l'augmentation de la concentration de ces huiles, ainsi qu'une toxicité qui augmente avec la durée du traitement. De plus, la comparaison entre : 1. L'huile d'Allium cepa et l'Aloe vera a montré que l'huile d’Allium cepa est la plus efficace. 2. L'huile d'Allium cepa et le mélange (Allium cepa + Aloe vera) a montré que l'huile d’Allium cepaest la plus efficace. 3. L'huile d'Aloe vera et le mélange (Allium cepa + Aloe vera) ont montré que le mélange (d'Allium cepa + l'Aloe vera) était efficace. 4. L'huile d'Allium cepa, l'Aloe vera et le mélange (Allium cepa + Aloe vera) a montré que l'huile d’Allium cepaest la plus efficace. Les tests de toxicité effectués ont montré que ces huiles ont des propriétés insecticides et que l'huile d’Allium cepaest le plus efficace par rapport aux autres huiles